2014
DOI: 10.21091/mppa.2014.2015
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Pain Among Polish Music School Students

Abstract: OBJECTIVE: To assess the prevalence and intensity of musculoskeletal pain and to estimate probability of developing playing-related musculoskeletal disorders, depending on risk factors, including gender, years of playing the musical instrument, frequency of practice (number of days per week), average daily practice time, and habitual physical activity level, in young instrumentalists. METHODS: A total of 225 instrumentalists aged 10–18 years, including 107 string-players, 64 keyboardists, and 54 wind-players,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 0 publications
5
44
0
8
Order By: Relevance
“…Concerning gender, females were found to be more vulnerable to PRP problems. This is in keeping with the majority of previous studies reporting that females are more frequently affected at student 8,10,17,18,21,24,[28][29][30][31][32] and professional levels. 15,33 With respect to age, age of onset of PRP, and hours of practicing, no gender differences were observed, suggesting that female susceptibility to PRP could be due to anatomical differences, such as less muscular strength, 9 joint laxity, hypermobility, 10,34,35 or hand muscle weakness.…”
Section: Playing-related Pain Issuessupporting
confidence: 91%
“…Concerning gender, females were found to be more vulnerable to PRP problems. This is in keeping with the majority of previous studies reporting that females are more frequently affected at student 8,10,17,18,21,24,[28][29][30][31][32] and professional levels. 15,33 With respect to age, age of onset of PRP, and hours of practicing, no gender differences were observed, suggesting that female susceptibility to PRP could be due to anatomical differences, such as less muscular strength, 9 joint laxity, hypermobility, 10,34,35 or hand muscle weakness.…”
Section: Playing-related Pain Issuessupporting
confidence: 91%
“…Some 22 studies also investigated the association between different MSS outcomes. Similar to the extent/severity studies, the majority (86%) of the studies of risk factors reported general symptom outcomes[27,28,30,38,[40][41][42][43][44][45][46][47][48][49][50]53,54,60,64,65,69,71,74,76,[79][80][81][82][83][84][85][86][87][88][91][92][93][95][96][97][106][107][108]110,111,115,116,119,122,125,126,[129][130][131][133][134][135][138][139][140][141][142][154][155]…”
mentioning
confidence: 99%
“…Em estudo realizado junto a população holandesa, Kok et al 3 observaram a ocorrência de sintomas osteomusculares em 89% de uma amostra composta por 83 musicistas, similar ao descrito por estudos conduzidos em países europeus [4][5][6] , África do Sul 7 e Austrália 8 . Observa-se ainda que o desenvolvimento de queixas osteomusculares é duas vezes mais frequente entre músicos quando comparados a população geral 3 .…”
Section: Introductionunclassified
“…Diversos fatores são elencados como agravantes para a saúde deste grupo profissional: a elevada exigência que o instrumento impõe ao corpo, incluindo alterações posturais impostas durante a prática musical e o transporte do mesmo 3,9 ; o início precoce da atividade, geralmente entre infância e adolescência 5 ; extenso período de prática musical e o acúmulo de funções do instrumentista dentro de uma orquestra sinfônica ou banda 10 .…”
Section: Introductionunclassified
See 1 more Smart Citation